ijee 2022
DOI: 10.48165/ijee.2022.58311
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use Profile of Farmers in Haryana

Abstract: Social media are digital networks that are used to share and discuss user generated informa tion - opinion, video, audio, and multimedia spreading far and wide even in remote areas of the country and has changed the way farmers communicate and interact. This study was conducted in 2021, with an objective to understand to understand the use of social media by farmers and to analyze its relationship with economic profile characteristic. The data were collected personally from Hisar and Sonipat districts of Harya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
1
3
0
Order By: Relevance
“…The findings of the present study were similar to the findings of Rezaei (2007) [18] Rajkumar (2009) [13] and Nambair (2013) [8] . The findings of the present study were similar to that of Sandika (2007) [20] , Mishra (2010) [6] , Madhavan (2015) [5] and Singh (2016) [22] . An overview of table 4 depicted that more than half (55.38%) of the Women Agriculture Officers belongs to rural areas followed by urban (44.62%) areas.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The findings of the present study were similar to the findings of Rezaei (2007) [18] Rajkumar (2009) [13] and Nambair (2013) [8] . The findings of the present study were similar to that of Sandika (2007) [20] , Mishra (2010) [6] , Madhavan (2015) [5] and Singh (2016) [22] . An overview of table 4 depicted that more than half (55.38%) of the Women Agriculture Officers belongs to rural areas followed by urban (44.62%) areas.…”
Section: Resultssupporting
confidence: 90%
“…The probable reason might be that a majority of Women Agriculture Officers were middle-age their children might be older enough to have depicted type of education status. [14] , Prabhavati (2012) [10] and Priyanka (2017) [6] . From table 13 it can be inferred that more than half (56.92%) of the Women Agriculture Officers had less number of dependents followed by medium (38.46%) and more number of dependents (4.62%).…”
Section: Resultsmentioning
confidence: 99%
“…experts who were working on the poisonous plants for dairy animals, were the scientists from the extension education division and pharmacology division in the study. Thirdly, "the method of data collection" under which personal interview method along with experts' consultation has been made for collecting the data as done earlier by Mishra (2022).…”
Section: Methodsmentioning
confidence: 99%
“…Kara (2018) analysed the content of websites, social media pages and mobile applications of agricultural product sellers and stated that marketing activities are available in new communication environments. Mishra et al, (2022) reported that in India watching videos was the most preferred purpose of social media use among farmers followed by chatting/ connecting with peers.…”
Section: Farmers' Social Media Usage Habitsmentioning
confidence: 99%